Representasi Perempuan Dalam Sinetron Suara Hati Istri - Aqila Mindani (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
This research aims to determine the representation of women in the Suara Hati Istri series using semiotic analysis from a gender perspective. This research was conducted using a narrative descriptive qualitative research method. The data in this research is the episode of “Beratnya Punya Suami Yang Ingin Istrinya Cantik Seperti Model” using data collection techniques browsing by the vidio.com site, documentation, and literature studies. This research uses Charles Sanders Peirce's semiotic analysis. The results of the research show that in the series of Suara Hati Istri: Beratnya Punya Suami Yang Ingin Istrinya Cantik Seperti Model women are represented based on the role of a wife, namely macak, masak, and manak in the patriarchal system of Javanese society. The character Nana is represented as a housewife who has complete responsibility for taking care of all the needs of the house, husband, and children. Her husband, Fendy, also demands that Nana continue to look beautiful. Apart from that, Fendy also considers that looking after and caring for children is a wife's responsibility so she is not allowed to have a baby sitter.